2017
DOI: 10.1371/journal.pone.0179688
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the HIV continuum of care among young black MSM

Abstract: BackgroundHIV disproportionately impacts young, black men who have sex with men (YBMSM) who experience disparities across the HIV care continuum. A more nuanced understanding of facilitators and barriers to engagement in care, missed visits, antiretroviral uptake, adherence and viral suppression could improve care and intervention design.MethodsA randomized controlled trial of an online intervention, healthMpowerment, enrolled 465 YBMSM (18–30 years); 193 identified as HIV-positive. Bivariable and multivariabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(52 citation statements)
references
References 58 publications
1
51
0
Order By: Relevance
“…Along with behavioural interventions , early HIV diagnosis and linkage to care and treatment , use of antiretroviral drugs as pre‐exposure prophylaxis (PrEP) is critical for the prevention of HIV acquisition . Clinical studies have demonstrated the efficacy of oral daily PrEP along with counselling in preventing HIV acquisition in MSM .…”
Section: Introductionmentioning
confidence: 99%
“…Along with behavioural interventions , early HIV diagnosis and linkage to care and treatment , use of antiretroviral drugs as pre‐exposure prophylaxis (PrEP) is critical for the prevention of HIV acquisition . Clinical studies have demonstrated the efficacy of oral daily PrEP along with counselling in preventing HIV acquisition in MSM .…”
Section: Introductionmentioning
confidence: 99%
“…There were no significant associations between marijuana use and ARV uptake, self-reported adherence, or viral suppression [35]. …”
Section: Resultsmentioning
confidence: 99%
“…However, studies have often focused on subgroups defined by age or race/ethnicity and rarely the intersection of these subgroups where YBMSM populations are positioned [14]. Further delineations of adolescent (13)(14)(15)(16)(17) and young adult (18)(19)(20)(21)(22)(23)(24) YBMSM communities are rarer still. Nevertheless, several factors described in existing studies may be important considerations for YBMSM.…”
Section: Hiv Testingmentioning
confidence: 99%
“…The efficacy of TasP and U=U depends on an intact and robust HIV care continuum including early diagnosis, care linkage, engagement, and sustained viral suppression among people living with HIV. However, YBMSM living with HIV are often less likely to be diagnosed, engaged in care, or virally suppressed compared with other age and race/ethnicity subgroups [21][22][23][24]. Several studies have examined barriers and facilitators of treatment engagement, adherence, and viral suppression in this population [21,[25][26][27][28].…”
Section: Biomedical Prevention Approachesmentioning
confidence: 99%